Guardians of Virtue: Historicizing the Evangelical Maternal Ethos and Exploring the Empowering Potentials of Religious Mother-Work - Reimer, Vanessa (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
This paper utilizes a theoretical framework of religious subcultural strength and maternal thinking to illustrate how mothers who operate within Western fundamentalist-evangelical Protestant subcultures are constrained by a maternal ethos to reproduce “acceptable” daughters who model ideals of “righteous” femininity. Inaddition to acting as children’s “natural” primary caregivers and ensuring their physical preservation and growth, these mothers are also designated as religious enculturators who are responsible for reproducing the next generation of “acceptable”Christians to propagate the subculture’s traditions and values. This task is particularly exacerbated for mothers of daughters who are charged with simultaneously modelling and reproducing ideals of “traditional” feminine purity and virtue, and who are consequently subject to blame and judgement when their daughters do not uphold these ideals. This paper seeks to historicize this evangelical maternal ethos by contextualizing it within Victorian discourses of “true womanhood.” It concludes by arguing that fundamentalist paradigms constrain maternal practice by holding mothers responsible for reproducing subcultural traditions, and it further considers the empowering potentials of religious mother-work then women and girls cultivate their spiritutalities from a place of agency, authenticity, and mutual enrichment.